ACUTE CARBOHYDRATE SUPPLEMENTATION IN WEIGHT TRAINING: A PILOT STUDY (Fiep Bulletin - online, 2014)
The purpose of this study was to analyze the effect of the acute ingestion of CHO on the physical acting during a session of weight lifting training. The subjects of this study were five individuals with 25,6 ± 3,2 years, that were submitted to two sessions of training with three exercises separated by three days. Both sessions consisted of the execution of four series in the intensity corresponding to 80% of 1-RM in the exercises, bench press, leg press 45° and arm curl, until the voluntary exhaustion. The interval among the series was of two minutes and five minutes among the exercises. The supplementation was conducted as double-blind model and randomized, where the ingestion of CHO (60g.L-1 maltodrextrina) or placebo (PL) (aspartame) accomplished in the proportion of 5ml.kg-1 occurring 15 minutes before the start of each session of weight lifting training. For the statistical analysis the test of Wilcoxon was used for non parametric samples, with level of significant of p=0,05. With our findings it can be observed that the ingestion of CHO didn't improve the performance in weight lifting training.
Keywords: supplementation; carbohydrate; weight training.